Evaluation of blood flow with heat transfer in human arteries through numerical modelling - Zhang, Zihao (Nanyang Technological University, 2020)
Carotid artery stenosis has become a common disease in today’s society. Evaluation through numerical modelling is one of the widely adopted approaches in biomedical related studies as it usually provides a solid basis at minimal cost. This study aims to evaluate blood flow with heat transfer and its relation to carotid artery stenosis through numerical modelling. Utilizing a numerical scheme with finite volume, a simulation of Systolic and Diastolic carotid artery flow inlet conditions is conducted with varying stenosis degree of 25%-90% in the carotid model. A study on 3-dimensional conjugate heat transfer is conducted on an ideal geometry of carotid artery, enclosed in a model representing the neck tissue of a human body. Varying temperature contours can be seen between non-stenosed and stenosed cases as the difference in the average temperature of the external surface of the neck skin is insignificant. The existence of a ‘cold region’ in the temperature of the external neck skin have been reported with more carotid artery stenosis cases on the rise. This numerical study will be helpful and have a strong basis for future evaluations with patients.